Stars and constellations - Hunter, Nick. (Chicago, Ill. : Capstone Heinemann Library, 2014)
This book explores the sun as our nearest star, different types of stars and constellations. It covers what stars are, where they come from, what makes them shine, what people thought of them in the past, and how we study stars today. A fun activity is provided along with advice on viewing stars. Beautiful photographs and simple text help to engage readers and aid their understanding.
Out of this world -- What are stars? -- Our own star -- What makes stars shine? -- Where do stars come from? -- Do stars last forever? -- Constellations -- Across the universe -- Exploring stars -- Visiting the stars -- Beliefs of the past -- See for yourself -- Finding constellations.
Includes bibliographical references (p. 31) and index.
2.9
K-3
700L
P
Center for the Collaborative Classroom Curriculum.
Keywords: Stars -- Juvenile literature; Sun -- Juvenile literature; Constellations -- Juvenile literature; Astronomy